Irina Dmitriyevna Yevtushenko - Article Editorial (Бюллетень сибирской медицины)
The creative biography and main directions of scientific and social activity of famous Russian obstetrician-gynecologist chief of Obstetrics and Gynecology Chair of Siberian State Medical University, Doctor of Medicine, professor I.D. Yevtushenko.